TRAINING OF ELECTRONIC RPP DEVELOPMENT FOR HEALTH ADMINISTRATION STUDY PROGRAM MANAGEMENT LECTURERS IN INDONESIA - Utami, Ressa Andriyani; Tamsuri, Anas; Marini, Ice (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The Learning Implementation Plan (RPP) is a plan that describes the procedures and organization of learning to achieve a basic competency set out in the Content Standards. Every educator in the education unit is obliged to prepare a complete and systematic RPP so that learning takes place interactively. The problem that occurs is that the preparation of the RPP is not optimal according to the provisions. The use of technology can be a new innovation in learning activities, starting from the preparation of lesson plans to the delivery of learning materials which we currently know with the online lecture method. The method used is training in the preparation of electronic lesson plans and at the end of the activity, an evaluation is carried out via google form. The results of the training activities showed that the implementation of the training and mentoring went well and received enthusiasm from the subjects. This electronic lesson plan preparation training is important because it helps lecturers prepare teaching materials so that the teaching and learning process becomes optimal.